Genesis 1 in the Book of "Jubilees" - VanderKam, James C. 1946- (2022)
The author of the Book of Jubilees rewrote the creation stories in Gen 1-2 and fashioned them in such a way as to stress several points: the importance of the Sabbath day, the idea that God alone, without assistance, created everything, and his conviction that God and Israel, who with the elite angels are the only ones who celebrate the Sabbath, are joined in a unique relationship of which the Sabbath is a sign.
Keywords: Creation; Exodus; Genesis; Genesis Rabbah; Isaiah; Jubilees; Philo; Sabbath; Angels